KAJIAN ETNOBOTANI INTARAN (AZADIRACHTA INDICA A.JUSS) - Sumerta, I. M.; Putri, D. M.S.; Sudiatna, I. N. (Buletin Udayana Mengabdi; Vol 21 No 1 (2022): Buletin Udayana MengabdiDO - 10.24843/BUM.2022.v21.i01.p03, 2022)
Ethnobotanical research on Intaran ( Azadirachta indica A. Juss.) has been conducted in Buleleng Regency, Bali. The studies conducted include botanical studies, ethnoecological studies, ethnopharmacology, ethnoanthropological, and technoeconomic, using the exploration method and interviews with community leaders, religious and cultural leaders, Balian and wood craftsmen. The results obtained indicate that the Intaran at the research site generally has a tree habit, its trunk can reach 20 meters or more, grows at an altitude of 1-300 m above sea level, on dry/barren soil with a soil pH of 4-6.5. The leaves and bark are used as a remedy for itching on the skin and an insecticide/worm control. This plant is also used in ritual facilities in traditional Hindu religious ceremonies, as a sacred building material for Hinduism, fodder for livestock and for soil conservation.   Keywords: Ethnobotany, Intaran, Buleleng